PERSEPSI MAHASISWA TERHADAP PEMBELAJARAN MATAKULIAH MATEMATIKA EKONOMI MELALUI MEDIA WHATSAPP GROUP - Imrona Hayati (STAI Sangatta Kutai Timur, 2021)
The importance of the existence of mathematics should be accompanied by a positive impression from students. However, the fact is that the majority of students show a negative impression at the beginning of the fourth semester learning process in February 2020. The negative impression of students on mathematics will have an impact on their low interest in learning and mastery of mathematics. Economic Mathematics learning since the Covid-19 pandemic was continued by using the Whatsapp media. A person's perception can differ from others depending on the processes and conditions and what experiences have been through. The purpose of this study was to determine students' perceptions of learning Economic Mathematics through the Whatsapp Group media. This type of research is descriptive. The instrument for obtaining data was in the form of a questionnaire which was distributed to 70 students of the Syari'ah Economics Study Program at STAI Sangatta, East Kutai, who have completed the Mathematics Economics course. The results of descriptive data analysis show that the majority of students have a positive perception of learning Economics Mathematics through Whatsapp Group media with a percentage ranging from 50% to 61%. If the learning of Economic Mathematics courses in the future will continue to be carried out using the Whatsapp Group media, many improvements must be made by referring to the analysis of the indicators in this study. Or the use of other learning methods and media that have been proven to bring maximum results can be used as an alternative, of course, still considering the suitability of student characteristics.